The micromeritics parameter changing of three inhalation dosage forms - Riswaka Sudjaswadi; Agatha Budi Susiana Lestari (Indonesian Journal of Pharmacy, 2005)
Droplet and particle size measurements obtained after spraying of three inhalation aerosols dosage forms by microscopic methods, had been carried out, and their distributions had also been reported.The results showed that the geometric mean diameter ( dg ) is getting higher since the first spray to the last. Whilst the geometric standard deviation ( τg ) fluctuated preferably to the moderate polydispersity.Key words : inhalation aerosols, geometric diameter and standard deviation